Here is the problem: e^(x+3) = (e^x) + 1

I use ln and get it to look like this: x + 3 = x but then what is the answer?

Printable View

- Sep 30th 2008, 04:21 PMShadowfox1logarithm problem
Here is the problem: e^(x+3) = (e^x) + 1

I use ln and get it to look like this: x + 3 = x but then what is the answer? - Sep 30th 2008, 04:45 PMJameson
Not quite right.

Look at it this way.

$\displaystyle e^{x+3}-e^x = 1$

$\displaystyle e^{x}*e^3 - e^x=1$

$\displaystyle e^x(e^3 - 1)=1$

$\displaystyle e^x= \frac{1}{e^3 -1}$

Got it from here? - Sep 30th 2008, 05:02 PMShadowfox1
o wow. I didn't even think to do that. thanks a lot.